330 Safety of abrocitinib in 3582 patients with moderate-to-severe atopic dermatitis with over 900 patients exposed for almost 2 years. (25th January 2023) - Simpson, Eric L; Silverberg, Jonathan I; Nosbaum, Audrey; Winthrop, Kevin; Guttman-Yassky, Emma; Hoffmeister, Karin M; Egeberg, Alexander; Valdez, Hernan; Fan, Haiyun; Farooqui, Saleem A; Chan, Gary; Alderfer, Justine; et al.
Abstract: Abrocitinib is an oral Janus kinase 1 inhibitor with demonstrated efficacy in moderate-to-severe atopic dermatitis (AD). To evaluate the long-term safety profile of abrocitinib and provide relevant information for practitioners. Data from patients who received ≥1 dose of abrocitinib 200 mg or 100 mg in the JADE clinical program were pooled in two cohorts. The consistent-dose (CD) cohort comprised patients who received the same abrocitinib dose during the entire exposure time in parent phase 3 studies and/or the long-term extension study JADE EXTEND (NCT03422822). Parent studies were: JADE MONO-1 (NCT03349060), JADE MONO-2 (NCT03575871), JADE TEEN (NCT03796676), JADE COMPARE (NCT03720470), JADE DARE (NCT04345367; 200 mg only) and JADE REGIMEN (NCT03627767); in JADE REGIMEN only patients from the open-label run-in phase (200 mg only) who did not subsequently enter the randomized phase were included. Patients from the phase 2b study (NCT02780167) were also included in the CD cohort. The variable-dose (VD) cohort comprised patients who received different doses of abrocitinib (200 and 100 mg) throughout exposure time in the parent study JADE REGIMEN and in JADE EXTEND, if enrolled. Patients included in the VD cohort completed the open-label period of JADE REGIMEN (abrocitinib 200 mg only) and entered the randomized phase (abrocitinib 200 mg, abrocitinib 100 mg or placebo); some patients subsequently entered the JADE REGIMEN rescue phase (abrocitinib 200 mg) and/or JADE EXTEND (abrocitinib 200 or 100 mg). The data cutoff was 16 April 2021. A Cox regression analysis evaluated risk factors for specific events of interest. Data from 3582 patients (4313.4 patient-years) were analysed: 2784 patients in the CD cohort (abrocitinib 200 mg, n = 1761, abrocitinib 100 mg, n = 1023) and 798 patients in the VD cohort. Duration of exposure was ≥48 weeks in 43.6%, 66.9% and 86.1% and ≥96 weeks in 18.0%, 23.2% and 45.4% of patients in the CD 200 mg, 100 mg and VD cohorts, respectively. In the CD and VD cohorts, the median age was 30.0 and 29.0 years; 490 (17.6%) and 145 patients (18.2%) were adolescents, and 143 (5.1%) and 30 patients (3.8%) were aged ≥65 years at screening, respectively. Incidence rates (IRs; unique patients with events per 100 patient-years) of serious adverse events (SAEs), deaths, and treatment-emergent adverse events of special interest are shown in Table 1 . IRs for SAEs were consistent across abrocitinib doses but were higher in patients aged ≥65 years vs. younger patients. Serious infections were the most frequent SAEs; frequency was not dose related. Herpes zoster (HZ), herpes simplex and pneumonia were the most frequent serious infections. From a Cox regression analysis, potential risk factors for treatment-emergent HZ included abrocitinib dose, baseline age, medical history of HZ, absolute lymphocyte count <1000 mm −3 prior to infection and region. Most (95%) adjudicated opportunistic HZ infections were cutaneous; 2 (5%) were extracutaneous (one serious disseminated varicella-zoster virus infection, one serious HZ meningitis). IRs for nonmelanoma skin cancer, malignancy (excluding nonmelanoma skin cancer), thrombocytopenia and lymphopenia were higher in patients aged ≥65 years vs. younger patients but were not dose related. Abrocitinib has an acceptable long-term safety profile in this large analysis of patients with moderate-to-severe AD. Risk of SAEs, HZ infection, malignancies and hematologic abnormalities increased with older age; HZ risk was also related to dose and prior HZ infection.